Anatomical Correlation Between Retinal Microvasculature and Coronary Artery Disease in a Pakistani Population. - Jamil, Farrakh; Naeem, Shabiha; Saqib Baloch, Muhammad; Mukhtar Qazi, Mansoor; Shahzad, Naeem; Amin Hashmi, Mashhood Shahid (Journal of Neonatal Surgery, 2025)
Background: The retinal microvasculature shares structural and physiological similarities with the coronary circulation and may provide a non-invasive window to assess systemic vascular pathology. Retinal vascular changes have increasingly been investigated as potential indicators of cardiovascular disease. This study aimed to evaluate the association between retinal microvascular anatomical changes and coronary artery disease (CAD) in a Pakistani population. Methods: A cross-sectional study was conducted at a tertiary care hospital in Pakistan including 120 participants aged 40–70 years. Sixty patients with angiographically confirmed coronary artery disease were included in the case group, while sixty age- and sex-matched individuals without known cardiovascular disease served as controls. Fundus examination and digital retinal photography were performed to assess retinal vascular parameters including arteriolar narrowing, arteriovenous (AV) nicking, vascular tortuosity, and retinal hemorrhages. Data were analyzed using descriptive and comparative statistical methods. Results: Retinal vascular abnormalities were significantly more frequent in patients with CAD compared with controls. Arteriolar narrowing was observed in 38 patients (63.3%) in the CAD group compared to 14 individuals (23.3%) in the control group. AV nicking was present in 31 patients (51.7%) with CAD versus 11 controls (18.3%). Increased retinal vascular tortuosity was detected in 26 CAD patients (43.3%) compared to 9 individuals (15.0%) in the control group. Retinal hemorrhages were identified in 12 patients (20.0%) with CAD, while only 3 participants (5.0%) in the control group demonstrated similar findings. The presence of multiple retinal microvascular changes was significantly associated with established coronary artery disease. Conclusion: Retinal microvascular anatomical changes were markedly more prevalent in patients with coronary artery disease in this Pakistani cohort. These findings support the concept that retinal vascular examination may serve as a useful, non-invasive tool for identifying individuals at increased risk of cardiovascular disease. Incorporating retinal vascular assessment into routine clinical evaluation may enhance early detection and risk stratification in populations with high cardiovascular burden..